Hyperinsulinemia augments endothelin‐1 protein expression and impairs vasodilation of human skeletal muscle arterioles - Mahmoud, Abeer M. (Physiol Rep, 2016)
Hyperinsulinemia is a hallmark of insulin resistance‐associated metabolic disorders. Under physiological conditions, insulin maintains a balance between nitric oxide (NO) and, the potent vasoconstrictor, endothelin‐1 (ET‐1). We tested the hypothesis that acute hyperinsulinemia will preferentially augment ET‐1 protein expression, disrupt the equilibrium between ET‐1 expression and endothelial NO synthase (eNOS) activation, and subsequently impair flow‐induced dilation (FID) in human skeletal muscle arterioles. Skeletal muscle biopsies were performed on 18 lean, healthy controls (LHCs) and 9 older, obese, type 2 diabetics (T2DM) before and during (120 min) a 40 mU/m(2)/min hyperinsulinemic‐euglycemic (5 mmol/L) clamp. Skeletal muscle protein was analyzed for ET‐1, eNOS, phosphorylated eNOS (p‐eNOS), and ET‐1 receptor type A (ETAR) and B (ETBR) expression. In a subset of T2DM (n = 6) and LHCs (n = 5), FID of isolated skeletal muscle arterioles was measured. Experimental hyperinsulinemia impaired FID (% of dilation at ∆60 pressure gradient) in LHCs (basal: 74.2 ± 2.0; insulin: 57.2 ± 3.3, P = 0.003) and T2DM (basal: 62.1 ± 3.6; insulin: 48.9 ± 3.6, P = 0.01). Hyperinsulinemia increased ET‐1 protein expression in LHCs (0.63 ± 0.04) and T2DM (0.86 ± 0.06) compared to basal conditions (LHCs: 0.44 ± 0.05, P = 0.007; T2DM: 0.69 ± 0.06, P = 0.02). Insulin decreased p‐eNOS (serine 1177) only in T2DM (basal: 0.28 ± 0.07; insulin: 0.17 ± 0.04, P = 0.03). In LHCs, hyperinsulinemia disturbed the balance between ETAR and ETBR receptors known to mediate vasoconstrictor and vasodilator actions of ET‐1, respectively. Moreover, hyperinsulinemia markedly impaired plasma NO concentration in both LHCs and T2DM. These data suggest that hyperinsulinemia disturbs the vasomotor balance in human skeletal muscle favoring vasoconstrictive pathways, eventually impairing arteriolar vasodilation.